The Quality Risk Assessment of Paralithodes Camtschaticus Collagenase Gel in the Process of Pharmaceutical Development - Ju. O. Ivankova; B. B. Sysuev; S. B. Evseeva (Разработка и регистрация лекарственных средств, 2023)
Introduction. The manufacturing and application of enzyme preparations in the semisolid topical products has features associated with their lability. In previous studies, on the set of specifications the gel form was selected, containing aerosil and olive oil, in which the stabilization of collagenase from Paralithodes camtschaticus was ensured by lipophilic base. In the pharmaceutical development process, the drug critical quality attributes must be defined. Taking into account the lability of Paralithodes camtschaticus collagenase, the identification and minimizing risks аre relevant.Aim. The aim was the risk factors assessment and minimization during the pharmaceutical development of the gel, containing Paralithodes camtschaticus collagenase within the QbD concept.Materials and methods. The laboratory samples of gels, containing Paralithodes camtschaticus collagenase, were tested, using the analysis methods recommended by the SP RF 14th ed., as well as GOST 29188.3-91.Results and discussion. Based on the potential critical characteristics of the material, the pharmaceutical substance Paralithodes camtschaticus collagenase (particle size) and excipients (concentration and sorption properties of aerosil, oxidation of olive oil) risk factors were assessed, and potential measures to reduce these risks are considered. It was revealed that the substance particle size in its origin exceeds the norm and requires preliminary grinding. The aerosil content factor was reveal as critical. The sorption properties of aerosil were not affected the proteolytic and collagenolytic activity of the collgenase gel. It was proved that chemical instability of oil refers to critical factors and the antioxidants (alpha-tocopherol or butylhydroxytoluene) content was justified.Conclusion. In the course of the study, the Paralithodes camtschaticus collagenase gel the possible risks of pharmaceutical substances and excipients were theoretically justified in accordance with the QbD concept. An experimental assessment of their possible impact on the gel quality was given, which can improve the finished product quality during manufacturing manufacturing by eliminating the identified risks.